Facial strategy for radical species through Ag(I)-mediated oxidation of the alkyl trifluoroborates. Issue 8 (18th April 2018) - Ding, Siyi; Tian, Shaopeng; Zhao, Yuzhen; Ma, Qiang; Zhu, Min; Ren, Huaping; Li, Kexuan; Miao, Zongcheng
ABSTRACT: A rapid and highly efficient method for the radical formation using potassium alkylfluoroborates as radical precursor is devised and developed which conducts under relatively mild condition using silver(I) oxide as the oxidant. The observed silver mirror phenomenon hints at the fact that Ag2 O is the real oxidant. This approach effectively overcomes the drawbacks-stringent reaction conditions and poor tolerance of a variety of functional groups. GRAPHICAL ABSTRACT: